ENSURING STUDENT-CENTERED, CONSTRUCTIVIST AND PROJECT-BASED EXPERIENTIAL LEARNING APPLYING THE EXPLORATION, RESEARCH, INTERACTION AND CREATION (ERIC) LEARNING MODEL - Matriano, Eric Agullana (International Online Journal of Education and Teaching, 2020)
Experiential learning literally is making meaning from direct experience. It plays vital role in facilitating the process of creating knowledge, sense-making and knowledge transfer in teaching, training and development. This study assessed the effectiveness of Exploration, Research, Interaction and Creation (ERIC) Learning Model which is a framework adopted from various theories and philosophies such those of student-centered, constructivist-based, project-based, experiential, multisensory, reflective, participatory, interactive, cooperative, collaborative and active learning. Mixed method was used employing pre-experimental design and narrative analysis of learning experiences. Pre-test and posttest, survey, interview, observation and focus group discussions were made. There were 32 college students in the Tourism Management Program enrolled in NAS 106 (Environmental Science) and 28 enrolled in BST 323 (Ecotourism) for Academic Year 2018 - 2019 at Columban College, Inc. and were used as subjects. Quantitative data were treated using Mean, Weighted Mean and t-Test for Dependent Samples. Student’s engagement and involvement were maximized by exploration, research, interaction and creation and they adapted the skills and strategies for them to become responsible learners and lifelong learners. There was a significant increase in the performance of students as well as develops more positive attitude towards the topics.